Mortality of Dalbergia sissoo in India - Shukla, A. N. (Indian Forester, 2002)
The reports of surveys conducted to assess the mortality of Dalbergia sissoo Roxb. in India are outlined. The possible reasons are discussed with particular reference to Fusarium solani (Mart.) Appel.& Wr. which is a secondary parasite on the dead roots and collaborative organism for the wilting of trees.